Comparative gastroprotective effect of Annona squamosa (atafol) leaf aqueous extract with omeprazole on ethanol induced gastric ulcer in Rats (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Annona squamosa is a fruit tree with long history of traditional use. Leaves of Annona squamosa have been reported to have gastroprotective effect.Objectives: The present work was conducted to evaluate the gastroprotective effect of Annona squamosa leaf on ethanol induced gastric ulcer in comparison to omeprazole.Study Design: To observe the gastroprotective effect of Annona squamosa leaf on ethanol induced gastric ulcer in rats an experimental study was done.Place and period of study: The study was conducted during July 2015 to June 2016 in the Department of Pharmacology & Therapeutics, Dhaka Medical College, Dhaka.Materials and Methods: A total number of 30 healthy Long Evan rats were used in this study. The experiment was divided into 2 parts: Experiment I and Experiment II. Experiment I was comprised of 12 rats: Group-A and Group-B having 6 rats in each group. Ulcer was produced by administration of absolute ethanol (1 mg/kg body wt.) in Group-B where Group-A served as control group and was provided with distilled water (5 ml/kg body wt.). All the rats were sacrificed after 60 minutes of ethanol administration, to confirm gastric ulcer by histopathology. Experiment II was comprised of 18 rats: Group-C, Group-D and Group-E having 6 rats in each group. Group-C served as disease control group and provided with distilled water (5 ml/kg body wt.). Group-D was provided with aqueous extract of Annona squamosa (500 mg/kg body wt.) and Group-E was provided with omeprazole suspension (10 mg/kg body wt.). After 10 days of treatment, animals were fasted for 24 hours. Then 1 ml of absolute ethanol (1 mg/kg body wt.) was administered and after 60 minutes all rats were sacrificed. Gross and microscopic examinations were performed to evaluate the results. Results: The mean ± SD of Lesion Index in Group C, Group D and Group E were 37.71 ±7.47 mm, 6.16 ±1.42 mm and 3.33 ±0.64 mm respectively. Statistically highly significant of difference was observed between Group C and Group D (P value < 0.001), between Group C and Group E (P value